2021
DOI: 10.1017/s1366728921000274
|View full text |Cite|
|
Sign up to set email alerts
|

Bilingual writing coactivation: Lexical and sublexical processing in a word dictation task

Abstract: Bilinguals’ two languages seem to be coactivated in parallel during reading, speaking, and listening. However, this coactivation in writing has been scarcely studied. This study aimed to assess orthographic coactivation during spelling-to-dictation. We took advantage of the presence of polyvalent graphemes in Spanish (one phonological representation with two orthographic specifications, e.g., / b /for both the graphemes v and b) to manipulate orthographic congruency. Spanish–English bilinguals were presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 129 publications
(194 reference statements)
0
9
0
Order By: Relevance
“…However, the first access to the word representation during writing‐to‐dictation assessed with performance in the first key performance (Iniesta, Paolieri, et al, 2021 ; Muscalu & Smiley, 2018 ) showed a clear dissociation between languages in monolinguals and bilinguals. That is, performance in Spanish was modulated by word length, whereas performance in English was modulated by word frequency and age of acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the first access to the word representation during writing‐to‐dictation assessed with performance in the first key performance (Iniesta, Paolieri, et al, 2021 ; Muscalu & Smiley, 2018 ) showed a clear dissociation between languages in monolinguals and bilinguals. That is, performance in Spanish was modulated by word length, whereas performance in English was modulated by word frequency and age of acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Bosse et al, 2003 ; Folk & Rapp, 2004 ; Roux & Bonin, 2012 ; Tainturier et al, 2013 ) showing a general influence of lexical (frequency and AoA) but also phonological (length and neighbours) variables in both languages during the later writing stage (rest of the word). However, during the early stage of writing (the first key; Iniesta, Paolieri, et al, 2021 ; Muscalu & Smiley, 2018 ), the transparent orthography (i.e. Spanish) biased processing towards phonological processing, whereas the opaque orthography (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations